Three New Polyynes from Codonopsis pilosula and Their Activities on Lipid Metabolism - Xiao-Yu Hu; Fu-Ying Qin; Xi-Feng Lu; Lan-Sheng Zhang; Yong-Xian Cheng (Molecules, 2018)
Three new polyynes, named choushenpilosulynes A–C (1–3), were isolated from an 85% aqueous EtOH extract of the roots of Codonopsis pilosula cultivated in Xundian County of Yunnan province, China. Their structures, including the absolute configuration of the glucose residue in 1 and 2, were determined by spectroscopic analysis and gas chromatography (GC). In addition, biological evaluation shows that all the compounds can inhibit the expression of the squalene monooxygenase (SQLE) gene in HepG2 cells, suggesting that these compounds may be involved in lipid metabolism.